Haemodynamic, Biochemical and Respiratory Implications of total Bronchoalveolar Lavage in Pulmonary Alveolar Proteinosis - Cartagena, María Nieves Balaguer; Tello, Ester Villareal; Pérez, Begoña Balerdi; Gómez, Andrés Briones; Tomás, Raquel Martínez; Viedma, Enrique Cases (Archives of Case Reports, 2023)
Introduction: Total bronchoalveolar lavage (BAL) continues to be the treatment of choice for alveolar proteinosis (AP), facilitating the removal of lipoprotein material. The purpose of this article is to evaluate the impact of haemodynamic, biochemical, and respiratory parameters, as well as the complications and evolution of patients undergoing this procedure. Methods: Retrospective, observational, and descriptive study of BAL. The technique was performed in the Intensive Care Unit. Blood gases, blood pressure, central venous pressure, body temperature, and fluid balance were analyzed. Results: Including eight patients, thirty-eight BAL were performed from 2008 to 2021. The mean instillation of saline at each session was 13.464 ± 4.002 ml per lung. No significant changes were observed before and after BAL in heart rate and blood pressure. Mean central venous pressure increased by 2.59 cm H20. The pO2 initial was 126 mmHg with a final mean of 69.7 mmHg, with statistical significance. The pCO2, HCO3 and pH parameters remained stable. Complications were observed during fifteen of the thirty-eight BAL (nine with arterial hypotension, three with glottic oedema, one acute pulmonary oedema, one pneumothorax, and one cardiorespiratory arrest). In terms of evolution, one case had a clinical-radiological resolution, one case of exits, one required lung transplantation, and the remaining five remained stable. Conclusion: This study demonstrates that the procedure, is well tolerated haemodynamically and that the biochemical alterations to which the patient is subjected are not compromised. With few complications and good results in delaying the progression of AP.